The The Effects of Clinical Supervision of Discussion Practicing Reflection Online Techniques on the Teachers’ Ability to Develop Tool of Scientific Learning Approach in Islamic Education - Arbaiyah Arbaiyah; Sukarno Sukarno; Minnah El Widdah (Universitas Kristen Satya Wacana, 2021)
This study aims to determine the effect of the Discussion Practice Reflection -online technique clinical supervision of the teacher's ability to develop Islamic religious education learning tools with scientific approaches. This study uses a quantitative approach with a quasi-experimental method through a quasi-experimental method with pretest and posttest designs. The sample in this study were teachers of Islamic religious education subjects at elementary schools in Bramitam District, West Tanjung Jabung Regency, Jambi province, with totaling 65 teachers. Based on the data and discussion, it can be concluded that the application of Discussion Practicing and Reflection-online technical clinical supervision has had a significant effect on the ability of Islamic Education teachers to develop learning tools with a scientific approach. Although the increase in ability was still dominated by an increase in the